The Monitoring by satelitte image to are and surface runoff in surrounding of governor office of west papua province: Monitoring by satelitte image to are and surface runoff in surrounding of governor office of west papua province - Ishak Semuel Erari; Edi Kuncoro Edi Kuncoro; Kwasti K. Kardiputra; Abdul Muis Muslimin (FMIPA Universitas Papua, 2024)
The development of Governor's Office of West Papua Province has cause change forest land area become using other land on the surrounding area, so that it has cause increasing the runoff surface wide and the coefficient of runoff . Objective of this study was for know development of the runoff surface wide and the average runoff coefficient with using satelitte image since 2010 to 2023. Results observation of satellite image that the runoff surface wide increase to 99.55 ha (56.25%) and average runoff coefficient increases from 0.32 to 0.56.